THE EFFECT OF ORGANIZATIONAL COMMUNICATION AND JOB SATISFACTION ON EMPLOYEE ENGAGEMENT AND EMPLOYEE PERFORMANCE AT PT. ABYOR INTERNATIONAL - Febrial Eka; Herminingsih Anik (Dinasti Publisher, 2020)
This study aims to analyze the effect of organizational communication and job satisfaction, on employee engagement and employee performance. The research data used are primary data derived from questionnaires and secondary data derived from company data. The sample method used is the nonprobability method. The population comes from all employees of PT. Abyor International which is still active in September 2019. The analytical method used in this study is the Partial Least Square (PLS) Structured Equation Model (SEM) using Smart PLS version 3.0. The results showed that organizational communication and job satisfaction had a positive and significant effect to employee engagement. Organizational communication and job satisfaction have no significant effect to employee performance. Employee engagement has a positive and significant effect to employee performance. Employee engagement becomes mediator for organizational communication and job satisfaction variables in influencing employee performance.